2021
DOI: 10.1021/acs.orglett.1c02962
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Three-Component Cascade Reaction of Nitriles: Synthesis of 2-Arylquinoline-4-carboxylates

Abstract: A new method for converting easy availability starting materials 2-(2-oxoindolin-3-yl)acetonitrile, arylboronic acids, and alcohols into 2-arylquinoline-4-carboxylates is reported. The procedure involves a three-component addition/ring expansion/ esterification reaction in the presence of Pd(II) catalyst with high functional group tolerance under mild conditions. In addition, the photophysical properties of the resulting product were investigated and exhibited excellent polarity-sensitive fluorescence properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…98 Recently, in 2021, an effective catalytic path to construct 2-arylquinoline-4-carboxylate ( 144 ) via a Pd( ii )-catalyzed addition/ring expansion/esterification reaction of 2-(2-oxoindolin-3-yl)acetonitrile ( 143 ), arylboronic acids, and alcohols was reported by Chen, Chen and Li's group (Scheme 72). 99 This strategy is successfully applied to access organic fluorescent carbazole-containing 2-arylquinoline-4-carboxylates, which showed excellent polarity-sensitive fluorescence properties and aggregation-induced emission (AIE) behaviour. Based on the experimental observations, a plausible mechanism for this cascade approach is proposed (Scheme 72).…”
Section: N- and O-heterocycles Via C−c And C−n Bond Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…98 Recently, in 2021, an effective catalytic path to construct 2-arylquinoline-4-carboxylate ( 144 ) via a Pd( ii )-catalyzed addition/ring expansion/esterification reaction of 2-(2-oxoindolin-3-yl)acetonitrile ( 143 ), arylboronic acids, and alcohols was reported by Chen, Chen and Li's group (Scheme 72). 99 This strategy is successfully applied to access organic fluorescent carbazole-containing 2-arylquinoline-4-carboxylates, which showed excellent polarity-sensitive fluorescence properties and aggregation-induced emission (AIE) behaviour. Based on the experimental observations, a plausible mechanism for this cascade approach is proposed (Scheme 72).…”
Section: N- and O-heterocycles Via C−c And C−n Bond Formationmentioning
confidence: 99%
“…Based on the experimental observations, a plausible mechanism for this cascade approach is proposed (Scheme 72). 99 Initially, transmetalation occurs with arylboronic acid and a Pd( ii ) catalyst to form an arylpalladium species ( A ), which is coordinated to the cyano group of 2-(2-oxoindolin-3-yl)acetonitrile to generate complex ( B ). After that, insertion of aryl to the cyano group generates an imine palladium complex ( C ), which is hydrolyzed to a dicarbonyl compound ( D ).…”
Section: N- and O-heterocycles Via C−c And C−n Bond Formationmentioning
confidence: 99%
“…9 In 2021, Chen et al demonstrated a Pd(II)-catalyzed three-component reaction of nitriles for the synthesis of 2arylquinoline-4-carboxylates involving addition and ring expansion, followed by esterification [Scheme 1(ii)]. 10 In 2017, a Cu(I)-catalyzed [2 + 2 + 2] synthesis of multisubstituted pyridines was developed by Chen's group, which was initiated via alkenylation of nitriles with vinyliodonium salts [Scheme 1(iii)]. 11 A similar [2 + 2 + 2] cycloaddition of α,ω-diynes with nitriles using Ir(I)-catalyzed is reported by the Takeuchi group to access pyridines [Scheme 1(iv)].…”
mentioning
confidence: 99%
“…In 2019, Chen and Shao’s group reported a Pd­(II)-catalyzed addition of arylboronic acids with 2-aminostyryl nitriles to access 2-arylquinolines [Scheme (i)] . In 2021, Chen et al demonstrated a Pd­(II)-catalyzed three-component reaction of nitriles for the synthesis of 2-arylquinoline-4-carboxylates involving addition and ring expansion, followed by esterification [Scheme (ii)] . In 2017, a Cu­(I)-catalyzed [2 + 2 + 2] synthesis of multisubstituted pyridines was developed by Chen’s group, which was initiated via alkenylation of nitriles with vinyliodonium salts [Scheme (iii)] .…”
mentioning
confidence: 99%
“…It is well-known that the Pfitzinger reaction is a traditional method for building a 2-arylquinoline-4-carboxylate core with strong bases and a high temperature . In recent years, a variety of novel synthetic approaches for preparing 2-substitued quinoline-4-carboxylate derivatives have been developed (Scheme ), including (a) cyclization of N -arylimines with ketonic acids, acrylates, or propiolates, (b) radical reaction of vinyl azides and α-carbonyl benzyl bromides, (c) [2+1+3] cyclization of 1,3-dicarbonyl compounds with aryl methyl ketones and arylamines, and (d) a three-component cascade reaction of 2-(2-oxoindolin-3-yl)­acetonitrile, arylboronic acids, and alcohols …”
mentioning
confidence: 99%